Synesthesia in Netizen Comments on the Video of the Song “Khanti” - Tanti Ariana; Triana Rahma Wulandari; Neneng Nurjanah (SUAR BETANG, 2023)
Synesthesia is a metaphor in the form of an expression related to the five senses used in a particular object or concept. Many people use language containing synesthesia to express something that has to do with human senses, especially in expressing impression over a song done by netizens in the form of comments. This study was conducted with the aim of disclosing and categorizing the types of synesthesia in netizen comments on the video lyrics of the song “Khanti”through the Rossa Official Youtube as the data source. The method used in this research is descriptive qualitative. The types of synesthesia are divided into five human senses, namely the sense of sight (eyes), the sense of smell (nose), the sense of taste (tongue), the sense of touch (skin), and the sense of hearing (ears). The results show that the sense of touch (skin) has the highest intensity of occurrence, which is 5 times. Thus, it can be concluded that the expressions containing metaphors in the comments are more likely to perceive the sense of touching the skin than the other senses. AbstrakSinestesia adalah metafora berupa ungkapan yang berhubungan dengan suatu pancaindra yang digunakan dalam suatu objek atau konsep tertentu. Banyak orang menggunakan bahasa yang mengandung sinestesia untuk mengungkapkan sesuatu yang memiliki kaitan dengan indra manusia, terlebih dalam mengungkapkan kesan terhadap sebuah lagu. Penelitian ini dilakukan untuk mengungkapkan dan mengategorikan jenis sinestesia yang terdapat dalam komentar warganet terhadap video lirik lagu “Khanti” melalui akun Youtube Rossa Official sebagai sumber datanya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Kategori jenis metafora sinestesia yang dideskripsikan terbagi ke dalam lima panca indra manusia, yaitu indra penglihatan (mata), indra penciuman (hidung), indra pengecap (lidah), indra peraba (kulit), dan indra pendengaran (telinga). Hasil penelitian menunjukkan bahwa indra peraba kulit memiliki intensitas kemunculan paling banyak, yaitu sebanyak 5 kali. Dengan demikian, dapat disimpulkan bahwa ungkapan yang mengandung metafora dalam komentar tersebut lebih cenderung memersepsikan indra peraba kulit dibandingkan indra lainnya.